The use of digital data for health regionalisation in Morocco: what contributions can it make to the implementation of the New Development Model? - Azzaz Fatima Ezzahra (International Journal of Scientific Research and Innovative Studies, 2024)
This study defends and analyses the strategic positioning that digital data can occupy in the realisation, within the framework of the orientations of the New Development Model (NMD), of health regionalisation in Morocco. The argument supported here, in the context of expectations regarding the governance of decentralised public policies and the digitalisation of the health system, is that the digitalisation of public policies and health systems promotes transparency, governance, coordination, and effectiveness of the health system. As such, this research aims, as its main objective, to assess the impact of digital data (electronic medical records, shared registers, and regional management platforms) on the performance of each institutional level and territory of the health systems in Morocco. This research aims, as its main objective, to assess the impact of digital data (electronic medical records, shared registers, and regional management platforms) on the performance of each institutional level and territory of the health systems in Morocco. The methodological approach adopted is quantitative, targeting a sample of 120 regional officials from the Ministry of Health and Social Protection. The research employs descriptive analyses, exploratory and confirmatory analyses using the SPSS and AMOS tools. The results obtained are linked to digital infrastructure, data quality, decision-making usage, and digital competencies of the doctrine and science in matters of the digitalised health system. In regional performance, these cumulative factors explain up to 69% of the variance. These observations indicate that the digitalisation process, beyond the technological aspects, acts as a tool for changing the governance of public administration techniques. It reinforces the autonomy of the regions, positively impacts health planning, and aligns with the objectives of the NMD. This paper concludes with comments on the strategic implications and perspectives of data-driven governance in the Moroccan health system. Keywords: digitalisation, digital data, health regionalisation, regional performance, New Development Model, Morocco. Received Date: February 26, 2024 Accepted Date: March 18, 2024 Published Date: April 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/475